2017
DOI: 10.1016/j.athoracsur.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Margins on Outcomes After Wedge Resection for Stage I Non-Small Cell Lung Cancer

Abstract: Increased margin distance was independently associated with lower risk of recurrence and longer overall survival in patients undergoing wedge resection for NSCLC tumors less than or equal to 2 cm. These findings suggest that with a minimum appropriate margin distance, wedge resection may yield outcomes comparable to those of lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…Analysis of prior data on sublobar resections from I-ELCAP institutions as well as others found that an increasing distance between the cancer and the margin of the resected specimen was associated with lower risk of recurrence (odds ratio ¼ 0.90; 95% confidence interval: 0.83 -0.98), and with longer lungcancer survival (hazard ratio ¼ 0.94; 95% confidence interval: 0.90 -0.98). 37 A margin size of 9 mm or more was associated with longest recurrence-free interval and a margin size of 11 mm or more was associated with the longest overall survival. To improve the standardization of margin assessment for sublobar resection, the IEL-CART protocol requires a measurement by each surgeon to be made in the operating room, in addition to the measurement routinely performed by pathologists on the surgical specimen.…”
Section: Current Practice For Treatment Of Early Small Nsclcsmentioning
confidence: 88%
“…Analysis of prior data on sublobar resections from I-ELCAP institutions as well as others found that an increasing distance between the cancer and the margin of the resected specimen was associated with lower risk of recurrence (odds ratio ¼ 0.90; 95% confidence interval: 0.83 -0.98), and with longer lungcancer survival (hazard ratio ¼ 0.94; 95% confidence interval: 0.90 -0.98). 37 A margin size of 9 mm or more was associated with longest recurrence-free interval and a margin size of 11 mm or more was associated with the longest overall survival. To improve the standardization of margin assessment for sublobar resection, the IEL-CART protocol requires a measurement by each surgeon to be made in the operating room, in addition to the measurement routinely performed by pathologists on the surgical specimen.…”
Section: Current Practice For Treatment Of Early Small Nsclcsmentioning
confidence: 88%
“…Yet, Mohiuddin et al . reported that in wedge resection for NSCLC, increasing the margin distance ≥15 mm significantly decreased the local recurrence risk, without evidence of additional benefit beyond 15 mm, while Wolf et al . found that a margin distance >11 mm was associated with longest overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…72 Even negative margins after wedge resections, if less than a centimeter, are associated with increased LRR and worse OS rates. 73 Sublobar resections are associated with higher rates of positive margins (wedge, 4.0%; segmentectomy, 2.1%; lobectomy, 1.4%; P < .001), inadequate nodal evaluation (fewer than 4 lymph nodes), and decreased median OS (wedge, 67.9 months; segmentectomy, 73.7 months; lobectomy, 94.5 months; P = .0008). 74 Stereotactic body radiotherapy (SBRT) is an alternative treatment option to surgery for patients with stage I NSCLC, especially those who have medical comorbidities that preclude surgery.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 94%
“…A trial in 975 patients who had resectable NSCLC reported that sublobar resection, stage IA or greater, squamous or large‐cell histology, and the presence of lymphovascular invasion were independently associated with higher rates of LRR on multivariate analysis . Even negative margins after wedge resections, if less than a centimeter, are associated with increased LRR and worse OS rates . Sublobar resections are associated with higher rates of positive margins (wedge, 4.0%; segmentectomy, 2.1%; lobectomy, 1.4%; P < .001), inadequate nodal evaluation (fewer than 4 lymph nodes), and decreased median OS (wedge, 67.9 months; segmentectomy, 73.7 months; lobectomy, 94.5 months; P = .0008) …”
Section: Non–small Cell Lung Cancermentioning
confidence: 99%